2022
DOI: 10.3390/ijms23116144
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic, Prognostic, and Mechanistic Biomarkers of Diabetes Mellitus-Associated Cognitive Decline

Abstract: Cognitive dysfunctions such as mild cognitive impairment (MCI), Alzheimer’s disease (AD), and other forms of dementia are recognized as common comorbidities of type 2 diabetes mellitus (T2DM). Currently, there are no disease-modifying therapies or definitive clinical diagnostic and prognostic tools for dementia, and the mechanisms underpinning the link between T2DM and cognitive dysfunction remain equivocal. Some of the suggested pathophysiological mechanisms underlying cognitive decline in diabetes patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 229 publications
0
42
0
Order By: Relevance
“…The results showed that the difference between ReHo and ICA/DC was not the primary source of heterogeneity. Previous studies have demonstrated that comprehensive background such as the age, course of disease, education level, emotional disorder, and biomarkers like HbA1c were related to cognitive impairment ( 142 , 143 ). In addition, the brain regions of cortical atrophy in patients with T2DM were also found in early Alzheimer's disease ( 144 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the difference between ReHo and ICA/DC was not the primary source of heterogeneity. Previous studies have demonstrated that comprehensive background such as the age, course of disease, education level, emotional disorder, and biomarkers like HbA1c were related to cognitive impairment ( 142 , 143 ). In addition, the brain regions of cortical atrophy in patients with T2DM were also found in early Alzheimer's disease ( 144 ).…”
Section: Discussionmentioning
confidence: 99%
“…Slowly progressive DCD occurs in all age groups, not limited to the aged population ( 30 ). The main pathological features of DCD include hyperphosphorylation of tau and apoptosis of hippocampal neurons, leading to progressive impairment of hippocampal function ( 31 33 ). A large number of DCD patients are more likely to present mild cognitive impairment (MCI) or dementia, showing a poor prognosis even after treatment ( 33 , 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main pathological features of DCD include hyperphosphorylation of tau and apoptosis of hippocampal neurons, leading to progressive impairment of hippocampal function ( 31 33 ). A large number of DCD patients are more likely to present mild cognitive impairment (MCI) or dementia, showing a poor prognosis even after treatment ( 33 , 34 ). Conventional treatment options for DCD include measurements for lowering blood glucose, lifestyle interventions, and cognitive rehabilitation training.…”
Section: Discussionmentioning
confidence: 99%
“…AD is more common in diabetic patients than in nondiabetic patients and it is associated with a higher incidence or mortality rate [ 12 ]. The development of dementia and other neurological disorders is common in T2DM, although a sporadic form of dementia is more common ( Table 1 ) [ 13 ]. The pancreatic islets contain alpha and beta cells, which regulate glucagon and insulin, respectively.…”
Section: T2dm and Dementiamentioning
confidence: 99%